Can affordability and innovation coexist for medicines?. (13th January 2020) - Colbert, Allison; Rintoul, Andrew; Simão, Mariângela; Hill, Suzanne; Swaminathan, Soumya
Abstract : Improved transparency is essential to determine what is fair